2018
DOI: 10.1111/jpn.12892
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of growth performance of three different indigenous goat breeds exposed to summer heat stress

Abstract: A study was conducted to assess comparatively the growth performance of three different indigenous goat breeds during exposure to summer heat stress. The primary objective of the study was to observe the heat stress impact on the growth performance based on the body weight changes, allometric measurements, growth hormone (GH) concentration and peripheral blood mononuclear cell (PBMC) Insulin-like growth factor-1 (IGF-1) mRNA expression pattern during the summer season in comparison with the local breed (Osmana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
(51 reference statements)
3
27
0
Order By: Relevance
“…A comparative study among tropical indigenous goat breeds (Osmanabadi, Malabari, and Salem black) showed differences in feed intake during the summer season, being reduced in Malabari animals but not the other breeds during heat stress [75]. Likewise, heat stress reduced feed intake in second-cross Merino (Poll Dorset × Merino/Border Leicester) lambs, but not Dorper lambs when both breeds were subjected to heat stress [92].…”
Section: Behavioral Adaptationmentioning
confidence: 98%
See 3 more Smart Citations
“…A comparative study among tropical indigenous goat breeds (Osmanabadi, Malabari, and Salem black) showed differences in feed intake during the summer season, being reduced in Malabari animals but not the other breeds during heat stress [75]. Likewise, heat stress reduced feed intake in second-cross Merino (Poll Dorset × Merino/Border Leicester) lambs, but not Dorper lambs when both breeds were subjected to heat stress [92].…”
Section: Behavioral Adaptationmentioning
confidence: 98%
“…A comparative assessment study between Baladi and Damascus goat breeds showed a greater rate of reduction in body weight in the latter (2.85% vs. 3.33%) under thermal challenge [74]. Pragna et al [75] also reported a reduction in body weight and body condition score among indigenous goat breeds under heat challenge, with the effect being greater in the Osmanabadi breed than Malabari and Salem Black breeds. Malabari and Salem Black breeds appear to tolerate arid conditions whilst sustaining productivity.…”
Section: Genetic Differences In Heat Tolerance In Small Ruminantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, further molecular mechanisms and physiological consequences of HS using an animal model are highly recommended.Previous studies have shown HS-induced physiological and biochemical variations in many animals, such as rats [10,11], cows [12], and chickens [13]. The HS causes an imbalance of glucocorticoids, the adrenocorticotropic hormone, the growth hormone, and the norepinephrine hormone, resulting in detrimental metabolic changes [10,14,15]. Furthermore, a set of proteins involved in the antioxidant stress response and inflammatory response, including catalase, glutathione peroxidase, and C-reactive protein were affected by HS [16][17][18][19].…”
mentioning
confidence: 99%